Characterization of phytochemicals of Clitorea ternatea and the potention as neuroprotectant to prevent Alzheimer's disease - WILDA BUNGA TINA SANJAYA; DEWI RATIH TIRTOSARI; RINI WIDAYANTI; DWI ARIS AGUNG NUGRAHANINGSIH; GOLDA RANI SARAGIH; HEVI WIHADMADYATAMI; DWI LILIEK KUSINDARTA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sanjaya WBT, Tirtosari DR, Widayanti R, Nugrahaningsih DAA, Saragih GR, Wihadmadyatami H, Kusindarta DL. 2025. Characterization of phytochemicals of Clitorea ternatea and the potention as neuroprotectant to prevent Alzheimer's disease. Biodiversitas 26: 3144-3159. Clitoria ternatea (Fabaceae), known by most as butterfly pea, is a significant medicinal plant recognized for its diverse bioactive compounds and therapeutic potential. The ethanolic extract of C. ternatea blume has shown promising neuroprotective effects, particularly in enhancing memory and reducing behavioural impairments. This plant, especially the section of roots and leaves, is recognized in traditional medicine and has been studied for its potential in treating neurodegenerative conditions. Meanwhile, there's still a lack of information for the therapeutic activities of its blume. Consequently, it is necessary to characterize the phytochemical compound of C. ternatea blume ethanolic extract to determine the neuroprotective potential. The phytochemical compounds were characterized by Ultraviolet-Visible spectroscopy (UV-VIS), Thin Layer Chromatography (TLC), Gas Chromatography-Mass Spectrometry (GC-MS), Fourier Transform Infra-Red (FT-IR), in silico molecular docking, and proliferation evaluation using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay on TMT-induced neurotoxicity Pheochromocytoma rat cell (PC-12). The result presented total phenol (12.28%b/b), total tannin (10.39%b/b), total flavonoid (4.54%b/b), total saponin (1.2%b/b), total steroids (8,019.81 µg/mL), total alkaloids (617.9 µg/mL), 33 active phytochemical constituents with palmitic acid composition reaching 17%, strong appearance displays in many functional groups including hydroxy compound, unsaturated/aromatic compound, saturated aliphatic (alkene/alkyl), skeletal C-C vibrations, and ether compound, in silico molecular docking shows that palmitic acid inhibits the accumulation of ?-amyloid, and C. ternatea reaches the optimum dose-dependent level of PC-12 cell proliferation at 31.25 µg/mL. Based on the results, C. ternatea ethanolic extract has significant potential as a neuroprotectant.